HUBUNGAN DISIPLIN DAN ETOS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI KASUS : PT TEXMACO KARAWANG) - Endang Hendrayanti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2004)
Employee’s productivities is the main goal for many business organization. So knowing the factors that will be influence employee’s productivities is mayor issues in HRD. This study examine whether disipline and working etos attained superior employee’s productivity. Disipline is variable of well being operative action in HRM so high level is needed. Good disipline described high responsibility for some one for jobs that is given to him. Work etos is thinking and felling that influence attitude and skill to someone. This factor are be more influence for getting the goals or not that individual or team needed in the organization. This reserch result indicate high relationship one positive significance influence for disipline and working etos for produclillty in Texniaco Karawang